ASEAN Regional Potentials for Combating COVID-19 - Rizky Widian; Vrameswari Omega W (Jurnal Ilmiah Hubungan Internasional, 2020)
The coronavirus disease (now known as COVID-19) has quickly spread across the world. Due to the rapid increasein the number of cases, COVID-19 has been declared by WHO as a global pandemic and has affected many aspectsof human lives. Various policies have been taken by the governments at the national level such as 'lockdown' policyor advanced social distancing. The threat of this global pandemic is transnational in nature, hence, regional andmultilateral cooperation would be required. In this case, ASEAN members have already discussed several collectivesteps at the regional level. Thus, this article intends to explore and elaborate on the potentials of ASEAN toencourage the realization of states' cooperation and commitments to fight the regional challenges under theoutbreak condition.